2021
DOI: 10.1073/pnas.2023942118
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional control of local auxin distribution by the CsDFB1-CsPHB module regulates floral organogenesis in cucumber

Abstract: Plant cystatins are cysteine proteinase inhibitors that play key roles in defense responses. In this work, we describe an unexpected role for the cystatin-like protein DEFORMED FLORAL BUD1 (CsDFB1) as a transcriptional regulator of local auxin distribution in cucumber (Cucumis sativus L.). CsDFB1 was strongly expressed in the floral meristems, floral primordia, and vasculature. RNA interference (RNAi)-mediated silencing of CsDFB1 led to a significantly increased number of floral organs and vascular bundles, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Subcellular localization of CsDULL followed the procedure described by Nie et al . [ 48 ]. In brief, the full-length coding sequence of CsDULL without the stop codon was cloned from cDNA of 2073-1 and inserted in the 35S::GFP expression vector (owned by our laboratory) to form a CsDULL–GFP fusion construct.…”
Section: Methodsmentioning
confidence: 99%
“…Subcellular localization of CsDULL followed the procedure described by Nie et al . [ 48 ]. In brief, the full-length coding sequence of CsDULL without the stop codon was cloned from cDNA of 2073-1 and inserted in the 35S::GFP expression vector (owned by our laboratory) to form a CsDULL–GFP fusion construct.…”
Section: Methodsmentioning
confidence: 99%
“…The SAM status of many plants and various characteristics have been observed by slices to further determine the growth and development period of plants and the function of genes ( Takagi and Ueguchi, 2012 ; Cheng et al., 2018 ; Nie et al., 2021 ; Olas et al., 2021 ). We used toluidine blue to dye the SAM of Chinese cabbage under different plumule-vernalization treatments combined with different flowering times after plumule-vernalization and selected representative periods NV, V5, V15, V25, and T3 for RNA-seq ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Flowering reversion is a phenomenon in which differentiated floral organs and tissues show a reversal of their development trajectories and enter vegetative growth again, which has been found in many species, including both monocotyledons and dicotyledons [ 8 , 44 ]. In the study of the molecular mechanism of floral organogenesis, scientists have found a variety of genes related to flowering reversion by investigating flowering reversion-related mutants and flower development [ 45 , 46 , 47 ]. However, flowering reversion is not simply the reversion of flower development but also may involve other novel biological regulatory processes.…”
Section: Discussionmentioning
confidence: 99%